Preservation of chemical and isotopic signatures within the Weißseespitze millennial old ice cap (Eastern Alps), despite the ongoing ice loss - Azzurra Spagnesi; Pascal Bohleber; Elena Barbaro; Matteo Feltracco; Fabrizio De Blasi; Giuliano Dreossi; Martin Stocker-Waldhuber; Daniela Festi; Jacopo Gabrieli; Andrea Gambaro; Andrea Fischer; Carlo Barbante (Frontiers in Earth Science, 2023)
Alpine ice core research has long focused on a few suitable drilling sites at high elevation in the Western European Alps, assuming that the counterparts at lower elevation in the eastern sector are unsuitable for paleoenvironmental studies, due to the presence of melting and temperate basal conditions. However, it has been demonstrated that even in the Eastern Alpine range, below 4,000 m a.s.l., cold ice frozen to bedrock can exist. In fact, millennial-old ice has been found at some locations, such as at the Weißseespitze (WSS) summit ice cap (Ӧtztal Alps, 3,499 m a.s.l.), where about 6 kyrs appear locked into 10 m of ice. In this work, we present a full profile of the stable water isotopes (δ18O, δ2H), major ions (Na+, K+, Mg2+, Ca2+, NH4+, Cl−, NO3−, SO42−), levoglucosan, and microcharcoal for two parallel ice cores drilled at the Weißseespitze cap. We find that, despite the ongoing ice loss, the chemical and isotopic signatures appear preserved, and may potentially offer an untapped climatic record. This is especially noteworthy considering that chemical signals of other archives at similar locations have been partially or full corrupted by meltwater (i.e., Silvretta glacier, Grand Combin glacier, Ortles glacier). In addition, the impurity concentration near the surface shows no signs of anthropogenic contamination at WSS, which constrains the age at the surface to fall within the pre-industrial age.